2013
DOI: 10.1007/s10661-013-3521-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evaluation of bioaerosols from indoor air of residential apartments within the metropolitan area in South Korea

Abstract: The aims of the present study were to determine the levels of bioaerosols including airborne culturable bacteria (total suspended bacteria, Gram-positive bacteria, Staphylococcus, Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), and Gram-negative bacteria), fungi, endotoxin, and viruses (influenza A, influenza B, respiratory syncytial virus types A/B, parainfluenza virus types 1/2/3, metapnemovirus, and adenovirus) and their seasonal variations in indoor air of residential apartments. Of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
6
36
2
Order By: Relevance
“…In our research, environmental parameters such as temperature, The non-significant difference between the (P) and (S) sites during the spring season may point to the influence of a common parameter on the bacterial aerosol levels. For example, increases in humidity and temperature are both associated with significantly higher culturable bacteria and fungi concentrations in indoor air [13]. In our research, environmental parameters such as temperature, RH, and CO 2 concentrations in both indoor and outdoor air during the sampling periods were measured to estimate the influence of these factors on bioaerosol levels.…”
Section: Total Concentration Of Bacterial and Fungal Aerosolsmentioning
confidence: 97%
“…In our research, environmental parameters such as temperature, The non-significant difference between the (P) and (S) sites during the spring season may point to the influence of a common parameter on the bacterial aerosol levels. For example, increases in humidity and temperature are both associated with significantly higher culturable bacteria and fungi concentrations in indoor air [13]. In our research, environmental parameters such as temperature, RH, and CO 2 concentrations in both indoor and outdoor air during the sampling periods were measured to estimate the influence of these factors on bioaerosol levels.…”
Section: Total Concentration Of Bacterial and Fungal Aerosolsmentioning
confidence: 97%
“…Though it has been reported that geographical locations affect the concentrations of endotoxins (Delfino et al, 2011;Kallawicha et al, 2015) and that airborne endotoxin concentrations tended to be higher during the autumn and spring seasons (Mazique et al, 2011;Moon et al, 2014), and higher in the summer than the winter season (Tager et al, 2010;Wheeler et al, 2011;Pavilonis et al, 2013;Bari et al, 2014), the results of the reviewed studies data on the possible effects of climate factors, such as humidity and temperature on endotoxin levels in both indoor air and settled dust were contradictory. Several studies found that higher relative humidity leads to higher airborne endotoxin levels (Park et al, 2000;Wickens et al, 2003b), and it has been suggested that relative humidity may be an important factor for controlling endotoxin exposure indoors (Park et al, 2000).…”
Section: Climate Factorsmentioning
confidence: 99%
“…During the two decades, many studies (Pastuszka et al 2000;Pastuszka et al 2005;Bernstein et al 2008;Aydogdu et al 2010;Nasir and Colbeck 2010;Pegas et al 2010;Salleh et al 2011;Dumała and Dudzińska 2013;Moon et al 2014;Karottki et al 2015) carried out in a variety of indoor environments showed a great variation in total concentration of air pollutants. Given the potential of airborne bioaerosols to cause disease, information on the total concentration of bioaerosol particles is insufficient.…”
Section: Introductionmentioning
confidence: 99%